La solidaridad: nuevas utopías en la moral social y en la economía. A propósito de la encíclica Caritas in Veritate - Rojas, Leonardo (2023)
The crisis in the economic and financial system poses new logics of understanding, seeking to recover alternative ways of development, thus, enabling that the dreams of another different world are still possible. It is not, therefore, to rescue a model that has become decadent and scandal, leading to the accumulation of capital in few hands, while vast majorities increase their misery. It is necessary to outline the necessary elements for understanding the current “social system” that makes difficult the future options that manipulates reality from the individualism and isolation. It should, therefore, explain a proposal to generate meaningful and significative alternatives of social life and the responsibilities of the human economy. Issues that are attracted by the Magisterium of the Church in Caritas in veritate. Perhaps, has our life a different meaning and a moral obligation from building a more just world for all?